Proceedings of the 5th International Conference on PErvasive Technologies Related to Assistive Environments 2012
DOI: 10.1145/2413097.2413130
|View full text |Cite
|
Sign up to set email alerts
|

User activities outlier detection system using principal component analysis and fuzzy rule-based system

Abstract: In this paper, a user activities outlier detection system is introduced. The proposed system is implemented in a smart home environment equipped with appropriate sensory devices. An activity outlier detection system consist of a twostage integration of Principal Component Analysis (PCA) and Fuzzy Rule-Based System (FRBS). In the first stage, the Hamming distance is used to measure the distances between the activities. PCA is then applied to the distance measures to find two indices of Hotelling's T 2 and Squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The evaluation is based on real-world data consisting of 431 traces of normal daily activities and 112 anomalous traces. We also found feature reduction method principal component analysis (PCA) with fuzzy rule-based system [26], [29], that is successfully applied to recognize the anomalous behavior of the user inside the home environment. Fuzzy rulebased system is based on three steps.…”
Section: ) Machine Learning Methodsmentioning
confidence: 99%
“…The evaluation is based on real-world data consisting of 431 traces of normal daily activities and 112 anomalous traces. We also found feature reduction method principal component analysis (PCA) with fuzzy rule-based system [26], [29], that is successfully applied to recognize the anomalous behavior of the user inside the home environment. Fuzzy rulebased system is based on three steps.…”
Section: ) Machine Learning Methodsmentioning
confidence: 99%
“…The IIE relies solely on non-intrusive sensors such as door and infrared motion sensors; research has proven that the use of intrusive technology such as surveillance cameras for patient monitoring is generally not accepted [9]. The sensors produce long series of binary multidimensional data that are difficult to analyse and manipulate manually, so a combination of Principal Component Analysis and Fuzzy Rule-based Systems are applied to process the data and identify and also predict deviations from normal behaviour pattern [10], which are relayed to the health clinicians and the patient carer. The research documented in this paper attempts to correlate the identified behavioural patterns to the symptoms of Dementia with the long term objective of developing a semantically-enabled Dementia care decision support system (DCDSS) that can aid health clinicians in the remote assessment of the patients' condition, and thus reduce the demand for on-site care and support longer independent living for the Dementia sufferers.…”
Section: Motivationmentioning
confidence: 99%
“…Research in the field of digital image filtering has been adapted for point cloud filtering algorithms but it is not direct due to the irregularity, shrinkage and drifting of point clouds. In recent years, a number of filtering methods for 3D point cloud have been developed, such as data clustering [12,13], density-based function [14,15], principal component analysis (PCA) [16][17][18], locally optimal projection (LOP) [19,20], MLS [21,22], nonlocal methods [23,24] and partial differential equations (PDEs) [25,26]. Zaman et al [14] proposed a point cloud denoising method based on a kernel density function.…”
Section: Introductionmentioning
confidence: 99%